Free‐Phase Gas Detection in Groundwater Wells via Water Pressure and Continuous Field Parameters. Issue 2 (21st September 2021) - Morais, Tiago A.; Ladd, Bethany; Fleming, Neil A.; Ryan, M. Cathryn
Abstract: Detection of free‐phase gas (FPG) in groundwater wells is critical for accurate assessment of dissolved gas concentrations and the occurrence of FPG in the subsurface, with consequent implications for understanding groundwater contamination and greenhouse gas emissions. However, identifying FPG is challenging during routine groundwater monitoring and there is poor agreement on the best approach to detect the occurrence of FPG in groundwater. In this study, laboratory experiments in a water column were designed to mimic nonflowing and flowing conditions in a groundwater well to evaluate how the presence of FPG affects water pressure and commonly used continuous field parameters. The laboratory results were extrapolated to interpret field data at an abandoned exploration well with episodic release of free‐gas CO2 . The FPG effect on water pressure varied between flowing and nonflowing wells, and depending on whether the FPG was above or below the sensor. Electrical conductivity values were decreased and/or behaved erratically when FPG was present in the water column. Findings from this study have shown that the combined measurement of water pressure, electrical conductivity, and total dissolved gas pressure can provide information about the occurrence of FPG in groundwater wells. Measurement of these parameters at different depths can also provide information about relative depths and amounts of FPG within the well water column. This approach can be used for long‐term monitoring of groundwater gases, managing gas‐locking in production wells with gassy groundwater, and measuring fugitive greenhouse gas emissions from groundwater wells.